Synergism and Antagonism between Bacillus thuringiensis Vip3A and Cry1 Proteins in Heliothis virescens, Diatraea saccharalis and Spodoptera frugiperda - Lemes, Ana Rita Nunes (Public Library of Science, 2014)

(untitled)
Second generation Bt crops (insect resistant crops carrying Bacillus thuringiensis genes) combine more than one gene that codes for insecticidal proteins in the same plant to provide better control of agricultural pests. Some of the new combinations involve co-expression of cry and vip genes. Because Cry and Vip proteins have different midgut targets and possibly different mechanisms of toxicity, it is important to evaluate possible synergistic or antagonistic interactions between these two classes of toxins. Three members of the Cry1 class of proteins and three from the Vip3A class were tested against Heliothis virescens for possible interactions. At the level of LC(50), Cry1Ac was the most active protein, whereas the rest of proteins tested were similarly active. However, at the level of LC(90), Cry1Aa and Cry1Ca were the least active proteins, and Cry1Ac and Vip3A proteins were not significantly different. Under the experimental conditions used in this study, we found an antagonistic effect of Cry1Ca with the three Vip3A proteins. The interaction between Cry1Ca and Vip3Aa was also tested on two other species of Lepidoptera. Whereas antagonism was observed in Spodoptera frugiperda, synergism was found in Diatraea saccharalis. In all cases, the interaction between Vip3A and Cry1 proteins was more evident at the LC(90) level than at the LC(50) level. The fact that the same combination of proteins may result in a synergistic or an antagonistic interaction may be an indication that there are different types of interactions within the host, depending on the insect species tested.